Soil aggregate formation and carbon storage by endogeic earthworms in an Ultisol - Morejón Centeno, Mauricio Renato (2025)
The role of soil micro and macro-organism in the incorporation of carbon to soil aggregates of tropical soils has been understudied. To test soil aggregate formation and carbon incorporation by earthworm activity, we conducted a field experiment within a secondary forest and a microcosm experiment at the University of Puerto Rico in Mayagüez. We used 13C natural abundance in vegetation and the difference in 13C between C3 and C4 plants to track carbon sources in the soil. Maize leaves were utilized to trace the incorporation of C4 carbon within soil aggregates, allowing for a clear distinction between this carbon source and the C3 carbon derived from forest vegetation. Earthworms and soil samples (Typic Haplohumults) were collected at 0-10 cm soil depth. Aggregates size classes were separated by the wet sieving method. In the study site, two earthworm species were found belonging to epigeic and endogeic ecological categories. In a period of 6 months, our field data suggests that endogeic P. corethrurus can reorganize small macroaggregates to form large macroaggregates. Our results suggest that P. corethrurus shows a preference for consuming soil-derived carbon and can translocate it from microaggregates to macroaggregates by restructuring soil aggregates.